2014
DOI: 10.1111/resp.12367
|View full text |Cite
|
Sign up to set email alerts
|

Obesity hypoventilation syndrome in Japan and independent determinants of arterial carbon dioxide levels

Abstract: The prevalence of OHS in OSA in Japan was 2.3%. The mean BMI of patients with OHS in Japan was lower than that in Western countries (36.7 kg/m(2) vs 44.0 kg/m(2) ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 30 publications
0
27
0
2
Order By: Relevance
“…OHS is seen much more commonly in sleep disorders clinics, with estimated prevalence ranging from 9 to 20% of referred obese patients, and as high as 42% of referred patients with a BMI more than 35 kg/m 2 [7,8 && ]. Multiple recent epidemiologic studies confirm similar rates of OHS: 10-17% of referred patients in Europe [9], 12.3% of obese patients with OSA in Japan [7], 8.5% of all referred patients, and 21% of referred patients with BMI more than 40 kg/m 2 in Saudi Arabia [8 && ], and as high as 51% prevalence in a population of obese patients with chronic hypoxemia in Canada [10]. Rates are even higher in the in-patient setting, with reported prevalence of OHS in 30-60% of patients with a BMI more than 50 kg/m 2 [6,11 & ].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…OHS is seen much more commonly in sleep disorders clinics, with estimated prevalence ranging from 9 to 20% of referred obese patients, and as high as 42% of referred patients with a BMI more than 35 kg/m 2 [7,8 && ]. Multiple recent epidemiologic studies confirm similar rates of OHS: 10-17% of referred patients in Europe [9], 12.3% of obese patients with OSA in Japan [7], 8.5% of all referred patients, and 21% of referred patients with BMI more than 40 kg/m 2 in Saudi Arabia [8 && ], and as high as 51% prevalence in a population of obese patients with chronic hypoxemia in Canada [10]. Rates are even higher in the in-patient setting, with reported prevalence of OHS in 30-60% of patients with a BMI more than 50 kg/m 2 [6,11 & ].…”
Section: Introductionmentioning
confidence: 62%
“…This finding is in contrast to prior concepts of OHS demographics, and epidemiologic data supporting OSA as a predominantly male affliction prior to the age of menopause in women [6,8 && ]. Harada et al [7] demonstrated similar rates of OHS between Japanese men and women (12.3%) and BaHammam reported a higher incidence of OHS with OSA in Saudi women (15.4%) versus men (4.5%) [8 && ]. There is no known OHS prevalence difference between racial or ethnic groups.…”
Section: Introductionmentioning
confidence: 93%
“…There is no widely accepted screening tool for ventilatory failure associated with SDB, although a number of studies limited to patients with OHS has explored various physiological correlates. 4,[14][15][16][17][18][19] One of the most consistent signals for daytime hypercapnia is elevated serum bicarbonate. 4,[15][16][17][18] However, the use of a single bicarbonate measurement as a screening tool has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prevalence of OHS was 2.3% among Japanese patients with OSA. 8 However, in a study conducted at a tertiary health care facility in Turkey, 3.4% of patients who underwent arterial blood gas analysis had evidence of hypoventilation, and OHS accounted for 24% of these subjects. 9 …”
Section: Epidemiologymentioning
confidence: 98%